GABAergic networks jump‐start focal seizures. (8th April 2016) - de Curtis, Marco; Avoli, Massimo
Summary: Abnormally enhanced glutamatergic excitation is commonly believed to mark the onset of a focal seizure. This notion, however, is not supported by firm evidence, and it will be challenged here. A general reduction of unit firing has been indeed observed in association with low‐voltage fast activity at the onset of seizures recorded during presurgical intracranial monitoring in patients with focal, drug‐resistant epilepsies. Moreover, focal seizures in animal models start with increased γ‐aminobutyric acid (GABA)ergic interneuronal activity that silences principal cells. In vitro studies have shown that synchronous activation of GABAA receptors occurs at seizure onset and causes sizeable elevations in extracellular potassium, thus facilitating neuronal recruitment and seizure progression. A paradoxical involvement of GABAergic networks is required for the initiation of focal seizures characterized by low‐voltage fast activity, which represents the most common seizure‐onset pattern in focal epilepsies.